Thermal Behaviour of Pharmacologically Active Lithium Compounds - Tobón Zapata, Gloria Elena (2000)
The thermal decompositions of a series of simple lithium compounds (carbonate, sulfate, acetate, citrates, aspartates and glutamates) currently used in the treatment of manic-depressive psychosis and related disorders were investigated by means of TG and DTA measurements in oxygen atmosphere. Pyrolysis residues were characterized by infrared spectroscopy. The stabilities of the hydrates and intermediate phases generated during the degradation processes are discussed.